2020
DOI: 10.1002/14651858.cd009645.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation (tDCS) for improving activities of daily living, and physical and cognitive functioning, in people after stroke

Abstract: Transcranial direct current stimulation (tDCS) for improving activities of daily living, and physical and cognitive functioning, in people a er stroke (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 185 publications
1
37
0
Order By: Relevance
“…Regarding brain plasticity, previous BCI studies have reported cortical reorganization alongside the clinical motor improvement ( 19 , 20 , 63 ). These results are thought to be partly due to the brain engagement needed for the BCI to work ( 64 ) and we hypothesize that the underlying plastic changes can further be enhanced with tDCS, which was reported to have a positive effect on the strength of event related desynchronizations ( 65 67 ) and motor outcome ( 68 , 69 ). We assume that behavioral restitution of function, induced by the combined neurotechnology approach will go alongside with cortical reorganization processes, which we plan to capture by a multimodal evaluation by means of (f)MRI, DTI and TMS-EEG related outcome measures.…”
Section: Discussionmentioning
confidence: 86%
“…Regarding brain plasticity, previous BCI studies have reported cortical reorganization alongside the clinical motor improvement ( 19 , 20 , 63 ). These results are thought to be partly due to the brain engagement needed for the BCI to work ( 64 ) and we hypothesize that the underlying plastic changes can further be enhanced with tDCS, which was reported to have a positive effect on the strength of event related desynchronizations ( 65 67 ) and motor outcome ( 68 , 69 ). We assume that behavioral restitution of function, induced by the combined neurotechnology approach will go alongside with cortical reorganization processes, which we plan to capture by a multimodal evaluation by means of (f)MRI, DTI and TMS-EEG related outcome measures.…”
Section: Discussionmentioning
confidence: 86%
“…From the past three decades, tDCS has become an increasingly popular technique in rehabilitation treatment (84). The use of tDCS in stroke research has gained particular interest, because both online and offline effects of tDCS can improve functional outcomes (85,86).…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%
“…[28][29][30] tDCS has gradually increased applicability in the neurorehabilitation field. [31][32][33][34]…”
Section: Clinical Application Of Tms and Tdcsmentioning
confidence: 99%